2008
DOI: 10.1113/expphysiol.2008.042788
|View full text |Cite
|
Sign up to set email alerts
|

Dose‐dependent cardiac effect of oestrogen replacement in mice post‐myocardial infarction

Abstract: Hormonal replacement therapy (HRT) has recently been shown to increase the risk of cardiovascular events in women. However, it is not clear whether the adverse effect of HRT is related to dosage and/or the presence of progestin. Using a mouse model of myocardial infarction (MI), we studied the dose-effect of oestrogen replacement on mortality and cardiac remodelling and dysfunction post-MI in the absence of progestin. Six-week-old females were subjected to ovariectomy (OVX). A pellet containing a low, moderate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
26
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 28 publications
(30 citation statements)
references
References 53 publications
4
26
0
Order By: Relevance
“…Our findings are in agreement with those of previous studies that reported cardioprotective effects of estrogen, which may involve inhibition of protein kinase C activity, mitogen-activated protein kinase signaling, and lactate dehydrogenase activity [34][35][36].…”
Section: Discussionsupporting
confidence: 95%
“…Our findings are in agreement with those of previous studies that reported cardioprotective effects of estrogen, which may involve inhibition of protein kinase C activity, mitogen-activated protein kinase signaling, and lactate dehydrogenase activity [34][35][36].…”
Section: Discussionsupporting
confidence: 95%
“…Estrogen has been shown to provide cardioprotection in various models of cardiac disease, including the aortocaval fistula model of heart failure (4,15,17,19,21,38,39,45,47).…”
Section: Discussionmentioning
confidence: 99%
“…38 However, whereas estrogen was found previously to inhibit collagen synthesis in cultured cardiac fibroblasts, 39 E 2 treatment enhanced myocardial infarction-induced cardiac fibrosis in mice. 40 Whether estrogen exerts protective or detrimental effects on the heart may thus depend on the dose and on animal species and strain.…”
Section: Discussionmentioning
confidence: 99%